A Better Place to Be- Reclaiming History for Political Theory - Christopher R. Binetti (Britain International for Academic Research (BIAR-Publisher), 2024)
This paper analyzes the periodization of Western history, broadly construed. It first divides the Old World (Asia, Africa, and Europe) into three macro-civilizations (or Civilizations), that are further broken down into micro-civilizations, or civilizations. The West covers the modern Middle/Near East, North Africa, Europe, and Central Asia. The East covers East Asia, including Mongolia, as well as Singapore and Vietnam. The Central Civilization covers South Asia and the rest of Southeast Asia. After making this division, the paper then breaks down Western history into basic periods, specifically for the purposes of Political Theory. Western history is broken up into nine basic periods, which form four ages, three epochs, and two eons. Ancient time is divided from Medieval-Modern time into two eons. Ancient time is then broken up into seven periods, forming three ages and two epochs, the latter group corresponding to the Bronze/Iron Age dichotomy. This system is devised specifically for Political Theory, and to a lesser extent, the rest of Political Science, in order to avoid biased from looking backwards at history, specifically those that divide the Greater Mediterranean world (a.k.a. the West) by modern religion.